2015
DOI: 10.1088/0960-1317/25/10/104006
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and characterization of a ceramic microcombustor with integrated oxygen storage and release element

Abstract: Manufacturing and characterization of a ceramic microcombustor with integrated oxygen storage and release element. Micromechanics and Microengineering, 25(10) Abstract -A microscale ceramic high-temperature combustor with a built-in temperature sensor and source of oxygen has been designed, manufactured and characterized. The successful in situ electroplating and oxidation of copper, and the use of copper oxide as the source of oxygen were demonstrated. It was shown that residual stresses from electroplating, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…The two different heater patterns used to achieve heating at central and peripheral areas, respectively, were designed based on thermography images of similar heater designs presented in [20]. Component thickness was chosen within the range of 300-1100 µm found for HTCC microcomponents in literature [8][9][10][11][12][13][16][17][18], many of which also contain cavities with single-sheet membranes [16,17,20,21].…”
Section: Design Of Generic Componentsmentioning
confidence: 99%
“…The two different heater patterns used to achieve heating at central and peripheral areas, respectively, were designed based on thermography images of similar heater designs presented in [20]. Component thickness was chosen within the range of 300-1100 µm found for HTCC microcomponents in literature [8][9][10][11][12][13][16][17][18], many of which also contain cavities with single-sheet membranes [16,17,20,21].…”
Section: Design Of Generic Componentsmentioning
confidence: 99%
“…A full description of the sintering profile can be found in [15]. Table 1 summarizes the main differences between methods A-D. …”
Section: Design Materials and Fabricationmentioning
confidence: 99%
“…For example microthrusters [12][13], microplasma sources [14], and a microcombustor for combusting solid minute samples prior to isotopic measurements of carbon [15], have been manufactured using HTCC. Integrating isolation valves in HTCC, is a step towards realizing a lab on a chip using this technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual gas analysis conducted during the combustion of a carbon-rich sample, together with microscopy, showed that oxygen released from the copper oxide reacted with the carbon, and formed carbon dioxide. [4] Figure 3. X-ray image of full-fledged combustor with a combined heater and oxygen supply meandering around the circular temperature sensor, inside which the sample inlet and gas outlet combine to make a bright circle (left), and microscope close-up of open reactor just after copper plating of the heater, not having affected the platinum temperature sensor (right).…”
Section: Component Overviewmentioning
confidence: 99%